Towards the Construction of a Personal Professional Pathway: An Experimental Project for the Recognition of Non-Formal and Informal Learning in the University of Catania. Issue 1 (May 2013) - Piazza, Roberta
In Italy, accreditation of prior learning is a sensitive issue. Despite the lack of laws or qualification frameworks regulating the recognition of non-formal and informal learning, most Italian universities proceed with caution, allowing only a restricted number of credits in the university curriculum related to practical activities or to external internships. The Faculty of Education of the University of Catania, partner in a Leonardo da Vinci project (2008–2010) regarding university placement services, has created an e-learning course for self-evaluation of non-formal and informal learning. The course, aimed at students attending their final year of a first level degree, has been set up as a support activity for students with low possibilities of entering the job market and not used to making the most of their learning experiences, especially if related to non-formal and informal settings. Ninety percent of these students are women from a low socio-cultural background with little experience or other qualifications. To date, modules have offered students useful tools to increase personal awareness in careers guidance, since the University of Catania cannot offer its students alternative opportunities.